Potential of Prenylated Flavonoid Derivatives from Jackfruit Roots (Artocarpus heterophyllus Lam.) as Liver Anticancer Candidates: In Silico Study - Richa Mardianingrum; Meylany Sity Rossy Lestary; Nur Aji; Ruswanto Ruswanto (Jurnal Kimia Sains dan Aplikasi, 2023)
Hepatocellular carcinoma (HCC), or liver cancer, is the fourth largest cancer in Indonesia, with 21,392 new cases and around 20,920 deaths. One of the standard drugs for liver cancer patients is lenvatinib, but lenvatinib has dangerous side effects such as hypertension. Previous studies reported that jackfruit root extract (Artocarpus heterophyllus Lam.) contains prenylated flavonoid compounds known to have anticancer activity. This study aims to find compounds that have the potential to the anticancer liver from jackfruit root by understanding the interaction between prenylated flavonoid derivative compounds against the VEGFR2 receptor (PDB ID: 3WZE) in silico. The methods include toxicity and pharmacokinetic screening, drug scanning, docking, and molecular dynamics simulation. The toxicity, pharmacokinetic, and drug scans of cycloartocarpesin are better than lenvatinib. The docking cycloartocarpesin compound showed ∆G -8.49 kcal/mol and Ki 0.59967 M lower than lenvatinib by forming the same hydrogen bond at residue Glu885. The molecular dynamics simulation of the cycloartocarpesin compound in the MM-GBSA calculation method resulted in a ∆Gtotal of -56.641 kcal/mol. The cycloartocarpesin compound is predicted to be used as a candidate for liver anticancer drugs because it has better stability and affinity than lenvatinib.